A legal study of a caretaker government in Malaysia / Abidah Ahmad, Ainil Farahin and Azlin Shahzwani - Ahmad, Abidah; Farahin, Ainil; Shahzwani, Azlin (Faculty of Law, 2012)
When a Parliament dissolves, caretaker government is a government which rules the country at that point of time. In Malaysia, a caretaker government is referring to the previous government which continues to take up the office in a caretaker capacity without the need of taking an oath. The question that comes into mind is that can a government which has lost its legitimacy rule the country? Is the establishment of a caretaker government hold on to the concept of democracy which allows the citizens to elect their own choice of leaders through general election? The only provision that is relevant with the establishment of a caretaker government is in Article 43(2) of the Federal Constitution. However, there is no mention of a caretaker government in the provision. The existence of a valid convention which has been adopted and applied in Malaysia can be said to have filled the lacuna of the law with regards to the caretaker government. By examining the relevant provision and the convention, it can be concluded that in Malaysia there is actually no law which particularly govern the establishment of a caretaker government. Apart from that, the discussion in this project paper is being extended on the strengths and weaknesses of the current legal framework of a caretaker government in Malaysia, Bangladesh and New Zealand. In doing so, it is observed that perhaps Malaysia can implement the suitable laws in Bangladesh and New Zealand as to accord the situations in Malaysia with regards to the establishment of a caretaker government.